Relationships Between Accuracy in Predicting Direction of Gravitational Vertical and Academic Performance and Physical Fitness in Schoolchildren - Haynes, Wayne; Waddington, Gordon; Adams, Roger; Isableu, Brice (Frontiers in Psychology, 2018)
Enhanced levels of both cardio-respiratory fitness (CRF) and physical activity (PA) are variables that are positively associated with health and academic outcomes, but less is known about the spatial processing and perceptual components of physical activity. Perception of vertical (PV) is a spatial orientation ability that is important for physical activity, and is usually measured as relative accuracy in aligning an object to gravitational vertical against a tilted background. However, evidence is inconclusive regarding the relationship of PV to educational outcomes – most importantly numeracy. Students were recruited from primary schools in the Australian Capital Territory a group of 341 (females n = 162, mean age 11.3 years) children performed all the tests required for this study. A computerised rod and frame test of PV employing a small (20°) visual angle was administered, and socio-economic status (SES), national education test results (NAPLAN), and CRF and PA data were collected. Correlation and hierarchical regression analysis were used to examine the inter-relationships between PV and CRF, PA, SES and NAPLAN results. Scores for the two extreme quartile groups from the measures of PV, PA and CRF were examined in relation to NAPLAN scores. PV scores arising from testing with a small visual angle and SES were found to be significantly associated with overall academic scores, and with the Numeracy, Reading and Writing components of academic performance. Female gender was significantly associated with Writing score, and male with Numeracy score. Being less influenced by the background tilted frame, and therefore having PV field independence, was associated with significantly higher academic scores, with the largest effect in Numeracy scores (effect size, d = 0.82) and with higher CRF and PA levels. Higher PV test scores were associated with all the academic modules examined, and most strongly with Numeracy test results, suggesting that PV score provides an indicator of STEM ability. These findings suggest that strategies for enhancing PV field independence deserve incorporation into the design of activity programs for pre-pubescent children. It is possible small visual angle spatial tasks during PA may stimulate neural networks involved in numerical cognition.